Alkene Hydrogenations by Soluble Iron Nanocluster Catalysts - Gieshoff, Tim N. (Angew Chem Int Ed Engl, 2017)
The replacement of noble metal technologies and the realization of new reactivities with earth‐abundant metals is at the heart of sustainable synthesis. Alkene hydrogenations have so far been most effectively performed by noble metal catalysts. This study reports an iron‐catalyzed hydrogenation protocol for tri‐ and tetra‐substituted alkenes of unprecedented activity and scope under mild conditions (1–4 bar H(2), 20 °C). Instructive snapshots at the interface of homogeneous and heterogeneous iron catalysis were recorded by the isolation of novel Fe nanocluster architectures that act as catalyst reservoirs and soluble seeds of particle growth.